Predictors of Persistent Post-Surgical Pain after Total Knee Replacement: A Systematic Review and Meta-Analysis of Observational Studies - Vahid Ashoorion; Behnam Sadeghirad; Li Wang; Atefeh Noori; Luciane C. Lopes; Yechan Kim; Yaping Chang; Meisam Abdar; Leila Nasiri; Mehdi Ghasemi; Nadia Rehman; Rachel Couban; et al. (Canadian Journal of Pain, 2019)
Introduction/Aim: Each year 67,000 Canadians undergo total knee arthroplasty (TKA) and approximately 20% develop persistent post-surgical pain (PPSP). A complaint associated with functional limitations, reduced quality of life, and increased care-seeking. We systematically reviewed observational studies to explore factors associated with PPSP after TKA. Methods: We searched Medline, EMBASE, Cochrane CENTRAL, AMED, PsycINFO, SCOPUS and SPORTDiscuss from inception to October 31, 2018. When possible, we pooled estimates of association for all independent variables reported by more than one study. Random effects models were used for all meta-analysis. We assessed certainty in evidence using the Grading of Recommendations Assessment, Development and Evaluation framework. Results: Twenty-five studies, involving 44,069 participants, were eligible for review. Mean age of enrolled patients was 68.56 ± 8.77 years and 76% were female. Eligible studies reported the association of 56 predictors with PPSP after TKA, which clustered into 6 groups: (1) patient characteristics, (2) clinical findings, (3) genetic factors, (4) surgical approach, (5) radiographic findings, and (6) peri-operative management. Low and very-low quality evidence showed that higher preoperative pain (OR = 3.82, 95%CI 1.27 to 11.47) and female sex (OR = 1.23, 95%CI 1.08 to 1.4) were significantly associate with PSPP after TKA. Neither older age (OR = 0.97, 95%CI 0.88 to 1.07), higher BMI (OR = 1.07, 95%CI 1.00 to 1.13), or mood disorders (OR = 1.14, 95%CI 1.0 to 1.3) were predictors of PPSP following TKA. Discussion/Conclusions: Addressing high peri-operative pain may be important in reducing PPSP after TKA.